Assessment in English Language Teaching: A Comprehensive Analysis (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Assessment is crucial in teaching English as a second language, determining students' growth and achievements. Formative and summative evaluations are used, with teachers adhering to standards like fairness, fairness, and legitimacy. Best practices include clearly expressing learning objectives, using various methods, providing clear criteria, and encouraging self-assessment. Challenges include ensuring fairness, considering language diversity, and addressing special needs. Technology and competency-based education offer opportunities, while recent developments provide valuable insights into students' language competency. Effective assessment methodologies can enhance English language education.